STUDENTS' LEARNING MOTIVATION FOR SEVENTH GRADE AT SMPN 3 TARAKAN IN MASTERING ENGLISH SPEAKING SKILLS - Grezela, Stefi Sesarimita; Ulfaika, Romlah; Ningtyastuti, Rina (Universitas Borneo Tarakan, 2022)
The purpose of this study was to describe the seventh-ninth grade students' learning motivation in mastering English speaking skills. The sample in this study were 27 seventh grade students. The material to be used in this study is qualitative material related to data that motivates seventh-ninth grade students to master English speaking skills. The data analysis used is: Qualitative Descriptive Analysis. As for the results of this study, the learning motivation of seventh-ninth grade students regarding the mastery of speaking skills (speaking) almost half of the students already have motivation. It can be seen from the results of the answers to the questionnaire filled out by the respondents that almost half of these students have motivation. Based on this research, some relevant learning implications and useful motivations are recommended to increase students' learning motivation in English.